Tailoring Metal Coordination in MOF‐Based Triple‐Layered Sealants for Gastric Hemostasis - Ruoyun Zhang; Xinyi Mao; Meiqi Wang; Luyao Zhang; Wenge Chen; Deyi Zhang; Zhangjie Pu; Guoqiang Li; Zhenzhen Zhu; Binglin Bie; Zhaowei Zhang (Advanced Healthcare Materials, 2026)
ABSTRACT Gastric perforation is one of the most difficult hemostatic scenes due to the extreme acidic environment, fragile tissue structure, and high risk of perforation leakage. A new series of sealants named M‐MOF‐74@Gel (M = Mg, Co, Ni, Cu, Zn) is invented for gastric perforation using a triple‐layered design including the exterior antibacterial layer, the middle layer of soft scaffold, and the interior thrombin‐like layer. Among these sealants, Zn‐MOF‐74@Gel sealant exhibits excellent biocompatibility near 95%, high efficiency of bacterial clearance (83.9% for Escherichia coli , 83.7% for Staphylococcus aureus ), strong adhesion (94 kPa), and fast hemostasis for liver and gastric perforation (60 s for liver, 100 s for gastric perforation). In addition, MOF‐74@Gel sealant can avoid the residue of MOF powder in trauma, adjust to the tissue shape, and inhibit the penetration of exterior aqueous solution. And the in vivo experiments further demonstrate the long‐standing flexibility in gastric perforation with adhesive block, resulting in no obvious leakage in the perforation channel. These enable the rats to successfully survive after surgery without dependence on antibiotics, indicating great potential for MOF‐74@Gel sealant in gastric perforation hemostasis.